"As I deeply understand the importance and greatly admire the poetry of experiment…"∗Cited from P N Lebedev's letter to N A Umov of 3 June 1896 [12, p. 135]. (on the eve of P N Lebedev's anniversary). (February 2016) - Shcherbakov, R N
Abstract: Whatever we think of the eminent Russian physicist P N Lebedev, whatever our understanding of how his work was affected by circumstances in and outside of Russia, whatever value is placed on the basic elements of his twenty-year career and personal life and of his great successes and, happily, not so great failures, and whatever the stories of his happy times and his countless misfortunes, one thing remains clear — P N Lebedev's skill and talent served well to foster the development of global science and to improve the reputation of Russia as a scientific nation.